Komik; Sebentuk Budaya Kreatif Perkembangan Sastra - Ulum Janah (Prologue: Journal on Language and Literature, 2021)
The development literature is inseparable from the medium used. Human creativity to package his work, in this case with regard to literature is a form of culture that also will not come off with the medium. One of the media used to pack the literary work is a visual medium. Furthermore, the literature is termed as "visual literature". Visual Literature is literature, particularly stories that poured into visual images. Examples of visual literature in Indonesia can be seen starting megalithic era until modern times that temple reliefs, Wayang Beber, up to the comic. Through visualization, particularly in the form of comic literature is packed using the language of images at once the language of text that can imitate the sound or motion that is not possible as long as written. Images are further highlight certain symbols also have a purpose that facilitates the reader's understanding of the various parties, groups, and levels.